Penerapan Business Intelligence Dalam Upaya Menigkatkan Penjualan dan Pemasaran Pakaian Pada CV. Ryan Bali Garment Berbasis Web - Wulan Ayu Safitri; Febri Hadi; Shary Armonitha Lusinia (Jurnal KomtekInfo, 2021)
Sales and marketing on CV Ryan Bali Garment is a problem that needs serious attention. Seeing the increase in sales, there is no increase in the web-based system built with the help of Business Intelligence analysis in the hope of finding out where the problems are that have an impact on sales. The system built aims to increase sales and marketing. In this study, researchers conducted analysis and testing of problems that arise which resulted in decreased sales so that the owner can directly take action to increase sales and marketing in that place. So that the system that is built can be a solution to the problems obtained.